PERAN SEKOLAH DALAM MENANGANI PRAKTIK PERUNDUNGAN DI MADRASAH IBTIDAIYAH - Sugiyanti, Annisa Mitra; Amaruddin, Hidar (Universitas Negeri Medan, 2023)
This study aims to describe and analyze in depth the role of schools in dealing with bullying practices at MI Ma'arif Sembego. Researchers used qualitative research with a descriptive approach. The subjects of this research are first-grade to sixth-grade teachers and the principal of MI Ma'arif Sembego. Data collection techniques used in-depth interviews, observation, and documentation. Interviews are used as a way for researchers to explore information in depth about the problems in the school being studied. The non-participatory observation was conducted to observe the handling of bullying practices by principals and teachers. Documentation of this research includes school profile biodata, photos, audiovisuals, and so on. Data analysis uses the Flow method from Miles & Hubberman in the form of three stages: data reduction, data presentation, and conclusion drawing. The results of this study show that dealing with bullying practices in schools through the role of principals and teachers can be divided into several indikators. The role of the principal becomes 4 indikators, namely leading, guiding, controlling, and providing school policies. Meanwhile, the role of the teacher is divided into 3 indikators, namely guiding, mediator, and counselor.